Weakening the Trade Unions, One Step at a Time: The Thatcher Governments' Strategy for the Reform of Trade-Union Law, 1979–1984. Issue 37 (September 2016) - Dorey, Peter
Abstract : This article examines the three statutes on trade-union law enacted by the Thatcher governments, 1979–84, and the discourse invoked to define the 'problem' and legitimize the legislation. Government papers reveal the thinking and the debates among ministers in relation to the trade-union 'problem'. James Prior favoured a minimalist approach, reflected in the Employment Act 1980. This was unacceptable to Margaret Thatcher and her closest colleagues and after his replacement by Norman Tebbit, the incremental approach was maintained, but the content of the laws had profound implications for the unions and their ability to engage in industrial action. The Employment Act 1982 narrowed the scope of a trade dispute, exposing trade-union funds to tort action (damages) for industrial action outside this new definition. The Trade Union Act 1984 imposed rules for the retention of this immunity. Reference was routinely made to the Trade Disputes Act 1906 as having placed the unions above the law by granting them a wide immunity from civil action for damages incurred during an industrial dispute. Hence the discourse of union 'privileges', and the need to place unions under the rule of law, just like any other individual or corporate body.